Intervensi Pendidikan Kesehatan Tentang Imunisasi IPV Pada Bayi Terhadap Pengetahuan Ibu - Mujiyanti, Sri; Puziasih, Anti Nopianti (Edu Masda Journal, 2023)
The IPV (Inactive Polio Vaccine) immunization is a mandatory primary immunization that should be administered to infants aged 4-11 months. Infants are at risk of contracting polio (poliomyelitis) if they do not receive IPV immunization. Maternal knowledge about IPV immunization is crucial to ensure that mothers can provide this immunization to their infants. This research aims to determine the impact of health education on IPV immunization for infants in the Carita Health Center's working area. This study employs a quasi-experimental design, specifically a one-group design without a control group. The instrument used is a questionnaire. The sample was selected using purposive sampling, with 53 respondents participating. Data were analyzed using the dependent t test The average pretest score was 8.17, while the average posttest score was 11.72. The difference in the average scores between the maternal knowledge pretest and posttest was -3.547. The paired t-test results showed a p-value of <0.001, indicating that there is an influence of health education on IPV immunization for infants on maternal knowledge in the Carita Health Center's working area. Therefore, there is a need for a change in the method and the addition of health education media in the form of colorful leaflets with accompanying pictures, to be distributed during every integrated health post activity.AbstrakImunisasi IPV (Inactive Polio Vaccine) adalah imunisasi dasar yang wajib diberikan kepada bayi usia 4-11 bulan. Bayi akan beresiko terkena penyakit polio (poliomyelitis) jika tidak diberikan imunisasi IPV. Pengetahuan ibu tentang imunisasi IPV sangat penting agar ibu dapat memberikan imunisasi IPV pada bayinya. Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan tentang imunisasi IPV pada bayi di wilayah kerja Puskesmas Carita. Penelitian ini menggunakan desain quasi eksperimen, one group without control.  Instrument yang digunakan berupa kuesioner. Teknik pengambilan sampel adalah purposive sampling sebanyak 53 responden.Data di analisis dengan menggunakan uji T dependen Hasil rata-rata pretest yaitu 8,17, rata-rata posttest yaitu 11,72. Hasil selisih rata-rata pengetahuan ibu pretest dan posttest -3.547. Hasil uji paired t-test diperoleh nilai p <0,001, yang berarti ada pengaruh pendidikan kesehatan tentang imunisasi IPV pada bayi terhadap pengetahuan ibu di wilayah kerja Puskesmas Carita. Perlu adanya perubahan metode dan penambahan media pendidikan kesehatan berupa leaflet yang berwarna disertai gambar dan diberikan  setiap kegiatan posyandu.